1978
DOI: 10.1007/bfb0069298
|View full text |Cite
|
Sign up to set email alerts
|

Wadge degrees and descriptive set theory

Abstract: The work to be presented here is taken principally from the three sources Steel [1977], Van Wesep [1977], and Wadge, listed in the bibliography.There is so far nothing published on this subject except the Van Wesep paper in the JSL.In Sections l, 2~ and 3 we provide a general picture of the Wadge degrees. In Section 4 we prove some results of Steel concerning functions from the Turing degrees to ~l modulo the Martin measure and apply them to a computation of the length of the Wadge ordering of A1 sets. Then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…Kechris has proved in ZF + DC that a class T and its dual f cannot both have uniform separation, provided that T is closed under 3W, VR, and continuous preimages. This gives a new proof of a weak form of Van Wesep's theorem [8] that AD implies T and T cannot both have separation. Harrington has proved that if ZFC is consistent then it is consistent with ZFC that both £í¡ and II3 have separation.…”
Section: Theoremmentioning
confidence: 87%
“…Kechris has proved in ZF + DC that a class T and its dual f cannot both have uniform separation, provided that T is closed under 3W, VR, and continuous preimages. This gives a new proof of a weak form of Van Wesep's theorem [8] that AD implies T and T cannot both have separation. Harrington has proved that if ZFC is consistent then it is consistent with ZFC that both £í¡ and II3 have separation.…”
Section: Theoremmentioning
confidence: 87%
“…He has also computed the rank ν of this structure which is a rather large ordinal. In [VW76,St80] the following deep relation of the Wadge reducibility to the separation property was established: For any Borel set A which is non-self-dual (i.e., A ≤ W A) exactly one of the principal ideals {X | X ≤ W A}, {X | X ≤ W A} has the separation property. The mentioned results give rise to the Wadge hierarchy which is, by definition, the sequence {Σ α } α<ν of all non-self-dual principal ideals of (∆ 1 1 (N ); ≤ W ) that do not have the separation property and satisfy for all α < β < ν the strict inclusion Σ α ⊂ ∆ β .…”
Section: Fh Of K-partitions and Wadge-like Reducibilitiesmentioning
confidence: 99%
“…Wadge also computed the corresponding (large) ordinal ν. In [4,5], it was shown that for any non self-dual Borel-Wadge class C, exactly one of the classes C or co(C) has the separation property (see [6]). Here, co(C) = {X | X ∈ C} is a dual class for C.…”
Section: Preliminariesmentioning
confidence: 99%